Laboratory evaluation of surface amendments for controlling greenhouse gas emissions from beef cattle feedlots - Aguilar, Orlando A.; Maghirang, Ronaldo G.; Trabue, Steven L.; Rice, Charles W.; Erickson, Larry E. (My University, 2013)
Pen surface amendments for mitigating emissions of greenhouse gases (GHGs), such as nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2), from beef cattle feedlots, were evaluated under controlled laboratory conditions. Amendments were organic residues (i.e., sorghum straw, prairie grass, woodchip), biochar from those organic residues and from beef cattle manure, and activated carbon. Manure samples were collected from several randomly selected pens from two beef cattle feedlots in Kansas and used in the experiments, either as dry (0.10 g · gˉ¹ wet basis water content) or moist (0.35 g · gˉ¹ wet basis). For each amendment, four different treatment levels (i.e., amounts of material) were placed on top of manure samples in glass containers and analyzed for GHG emissions using a photo-acoustic infrared multi-gas analyzer. From measured concentrations, emission rates were determined. For the dry manure conditions, all amendment materials showed significant reduction of N2O and CO2 emissions compared to the control (i.e., no amendment). For the moist manure conditions, none of the amendments showed significant effects on GHG emissions during the first 8 days; at days 10 and 15 after application, however, the biochar materials performed significantly better than the control (i.e., no surface amendment) in reducing N2O and CH4 emissions. No significant difference was observed in GHG emissions when the amendments were placed on top or mixed within the top surface layer of the manure.
Keywords: Biochar; Feedlot emission; Greenhouse gas emission; Greenhouse gas control; Organic residue; Surface amendment